Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1111/j.1439-0523.1989.tb00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Line × Tester Analysis Involving Diverse Cytoplasmic Systems in Sorghum

Abstract: Sorghun! h\'bnds. invoK'ini; three iso-stfrilc (A,, Aand Aai females and a set ot five feriilitv re.siorers. wcic evaluated loi-yield and yield ciimpanent.s in both rainy and ft-inter seasons. In i;eneral. .\.. C\-TOpiasm had larger i;rain size and hit;liei->-ii-ld [han traditional milu (.iXj cytoplasm and cytoplasm Aĥ ad an adverse efteci of vield and vield components. Cvtopiasmic s\-stcms also affected plant height, davs to bloom and i;rain size. Restorers IS f2567C, IS 12662C and SP\' 650 had desirable gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
(1 reference statement)
0
9
1
Order By: Relevance
“…These results are slightly different from other cytoplasm studies in sorghum wherein differences in grain yield were detected between different cytoplasms [23,25]. In these studies, the A3 cytoplasm was the poorest performing cytoplasm [24,32].…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…These results are slightly different from other cytoplasm studies in sorghum wherein differences in grain yield were detected between different cytoplasms [23,25]. In these studies, the A3 cytoplasm was the poorest performing cytoplasm [24,32].…”
Section: Resultscontrasting
confidence: 55%
“…In grain sorghum hybrids the effect of cytoplasm on performance of grain sorghum hybrids has varied, depending on study. Maves and Atkins [22] reported a reduction in grain yield in A2 hybrids compared to A1 hybrids while Kishan and Borikar [23] reported that A2 was superior to A1 for grain size and yield. Secrist and Atkins [24] found no significant differences in grain yield between A1 and A2 hybrid, but they reported a 6% reduction in grain yield in A3 hybrids compared to A1 hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Mahdy et al (1987) realized an increase in grain yield with significant heterosis by crossing among the superior families. Kishan and Borikar (1989) evaluated isosterile (A 1 , A 2 , and A 4 ) females and a set of five fertility restorers. Chen (1988) produced five homo-cytoplasmic and five heterocytoplasmic lines using 6-grain sorghum varieties with four types of cytoplasm.…”
Section: Extent Of Heterosis For Agronomic Physiological and Biochementioning
confidence: 99%
“…However, studies evaluating the agronomic potential of different CMS systems are inconsistent in their results. Kishan and Borikar (1988) reported that A2 is superior to A1 for grain size and yield while Maves and Atkins (1988) observed a yield decrease in A2 hybrids compared with A1 hybrids. Secrist and Atkins (1989) who found no significant differences ( P > 0.05) in grain yield between A1 and A2 hybrid, but they reported a 6% reduction in grain yield in A3 hybrids compared to A1 hybrids.…”
mentioning
confidence: 99%